2004
DOI: 10.1007/s00520-004-0694-2
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptom patterns and their consequences for diagnosis of affective disorders in cancer patients

Abstract: Cognitive symptoms should receive special attention in diagnostic procedures for affective disorders in cancer patients. In spite of possible symptom overlap with the cancer disease and its treatment, fatigue proves to be a useful criteria for diagnosis of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
(64 reference statements)
2
10
0
13
Order By: Relevance
“…This indicated that fatigue appears in conjunction with depression. These results are consistent with previous studies [43][44][45]. Sawada et al [46] found that many patients experienced fatigue and depression and their levels increased after beginning of the treatment.…”
Section: Discussionsupporting
confidence: 83%
“…This indicated that fatigue appears in conjunction with depression. These results are consistent with previous studies [43][44][45]. Sawada et al [46] found that many patients experienced fatigue and depression and their levels increased after beginning of the treatment.…”
Section: Discussionsupporting
confidence: 83%
“…Results show that the loss of interest question is somewhat better than the depression question when used alone. This corresponds to research showing that, of many symptoms of depression, loss of interest best discriminated between patients with and without diagnosis of comorbid affective disorder (Reuter et al, 2004). However, two questions are significantly better than any one question for detecting depression (Youden score was 0.78 for two questions, 0.54 for the depression question and 0.69 for the interest question).…”
Section: Discussionmentioning
confidence: 99%
“…Angesichts der uneinheitlichen Befundlage kann es kaum überraschen, dass auch hier die der Komorbidität zugrunde liegenden psychologischen und neurobiologischen Mechanismen noch weitgehend ungeklärt sind; es erscheint allerdings sehr wahrscheinlich, dass eine erhöhte Komorbidität primär auf die assoziierte Schmerzsymptomatik und Demoralisierung der Patienten zurückzuführen ist bzw. direkte oder indirekte Folge einer pharmakologischen Krebstherapie sein könnte [23].…”
Section: Krebserkrankungenunclassified